2021
DOI: 10.3389/fbioe.2020.631616
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Modifications of PEEK Implants for Bone Tissue Engineering

Abstract: In recent years, polyetheretherketone (PEEK) has been increasingly employed as an implant material in clinical applications. Although PEEK is biocompatible, chemically stable, and radiolucent and has an elastic modulus similar to that of natural bone, it suffers from poor integration with surrounding bone tissue after implantation. To improve the bioactivity of PEEK, numerous strategies for functionalizing the PEEK surface and changing the PEEK structure have been proposed. Inspired by the components, structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 151 publications
(152 reference statements)
0
38
0
Order By: Relevance
“…However, plasma-sprayed Ti coating to PEEK has shown direct bone ongrowth effect in long bone defect model in sheep. 139,140 Interestingly, a study demonstrates that porous Ti with a mean pore size of 279.9 ± 31.6 μm developed by melt extrusion method showed better osteogenic differentiation in vitro and superior implant osseointegration in vivo when compared to a plasma-sprayed Ti coated PEEK (0.13-0.25 mm thick layer of Ti) in a tibial bone defect rat model. 141 PEEK implants still lack the desired physical properties and osseointegration capacity to be clinically applied and are being rigorously tested and improved.…”
Section: Discussionmentioning
confidence: 99%
“…However, plasma-sprayed Ti coating to PEEK has shown direct bone ongrowth effect in long bone defect model in sheep. 139,140 Interestingly, a study demonstrates that porous Ti with a mean pore size of 279.9 ± 31.6 μm developed by melt extrusion method showed better osteogenic differentiation in vitro and superior implant osseointegration in vivo when compared to a plasma-sprayed Ti coated PEEK (0.13-0.25 mm thick layer of Ti) in a tibial bone defect rat model. 141 PEEK implants still lack the desired physical properties and osseointegration capacity to be clinically applied and are being rigorously tested and improved.…”
Section: Discussionmentioning
confidence: 99%
“…Pure HA, with its strong bond to native bone, is supposed to alter the bioinert surface of PEEK in a more favorable way regarding osseointegration [ 13 , 30 , 31 ]. However, a pure composite material will change the tensile strength of the bulk in an unfavorable way.…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrate a clinically relevant faster rate of fusion, based on postoperative plain radiographs, including flexion and extension views in the HA PEEK ACDF group. Furthermore, studies have shown enhanced bone growth in cortical and cancellous sites by incorporating HA into PEEK compared with PEEK alone [ 15 , 25 ], where investigators have reported the presence of a non-reactive fibrous tissue interface [ 26 , 27 ]. In addition, the HA at the surface of PEEK provides an osteoconductive surface, which supports bone apposition, thus improving rates of fusion clinically [ 25 ].…”
Section: Discussionmentioning
confidence: 99%